2018
DOI: 10.1021/acs.joc.7b03210
|View full text |Cite
|
Sign up to set email alerts
|

Directedortho-Metalation and Anionicortho-Fries Rearrangement of Polycyclic AromaticO-Carbamates: Regioselective Synthesis of Substituted Chrysenes

Abstract: A general method for the regioselective synthesis of a series of ortho-substituted chrysenyl N, N-diethyl- O-carbamates by the directed ortho-metalation (D oM) strategy is reported. The starting O-carbamates were prepared from the corresponding chrysenols, available by oxidative photochemical cyclization or directed remote metalation tactics. Chrysen-1-yl and chrysene-3-yl ring site selectivity of directed ortho-metalation (D oM) and anionic ortho-Fries rearrangement (A oF) protocols, with s-BuLi/TMEDA, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This was unanticipated as similar bromination on chrysenes with the N , N -diethylcarbamate directing group was reported in good yields. 60 Thereafter, I 2 was used as an electrophile; besides, iodo substrates are more reactive in the Suzuki–Miyaura cross-coupling. N , N -diethyl-2-iodochrysene-1-carboxamide ( 2a ) was obtained from 1a in excellent yield using s -BuLi/TMEDA and 1 M I 2 in THF ( Scheme 3 a).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was unanticipated as similar bromination on chrysenes with the N , N -diethylcarbamate directing group was reported in good yields. 60 Thereafter, I 2 was used as an electrophile; besides, iodo substrates are more reactive in the Suzuki–Miyaura cross-coupling. N , N -diethyl-2-iodochrysene-1-carboxamide ( 2a ) was obtained from 1a in excellent yield using s -BuLi/TMEDA and 1 M I 2 in THF ( Scheme 3 a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is worth mentioning, in this context, that our previous D o M study on chrysene-3-yl N , N -diethyl- O -carbamate with s -BuLi/TMEDA afforded only the C2-iodination product regioselectively in excellent yield. 60 In D o M reactions, s -BuLi (p K a = 51) and LiTMP (p K a = 37.3) 65 are the most commonly used bases. 66 In the present work, they were chosen over LDA (p K a = 35.7) 67 based on their base strength, for the previous studies reported p K a > 37.2 for ortho C–H bonds in monosubstituted benzenes with strong DMGs.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The metalation of arenes bearing an appropriate directing metalation group (DMG) with organolithiums or lithium amides, known as ortho-lithiation, nicely complements the classical electrophilic aromatic substitution, as well as other transition-metal-based methodologies mainly related with C–H activation reactions, for making regiospecifically functionalized aromatic rings. Among the oxygen-based DMGs employed for the functionalization of phenols, O -aryl carbamates have been recognized arguably as one of the most powerful DMGs, and usefully leading to phenol derivatives, with many applications in the synthesis of complex molecules . In addition, the carbamate group could undergo subsequent cross-coupling reactions under transition-metal catalysis …”
Section: Introductionmentioning
confidence: 99%